CRISPR therapy - revolution in medicine or ethical danger - Mielżyńska, Adrianna; Pograniczny, Mikołaj; Nalepka, Marcelina; Pochopień, Jakub; Pacołta, Adrianna; Golec, Jędrzej; Nowicka, Aleksandra (Quality in Sport, 2026)
CRISPR, or rather rarely used full name – Clustered Regularly Interspaced Short Palindromic Repeats. Studying this family of DNA sequences has led to the creation of CRISPR-Cas9 technology for genome editing. This technology has been with us for quite some time and is undeniably considered one of the most significant breakthroughs in modern genetics. It provides a powerful weapon for editing genomes with unprecedented precision, which can be used for advancing biotechnological inventions, finding and deploying new treatments and for overall progress in medicine. Recently, spikes of progress have been seen, which unquestionably have sparked many ethical and moral discussions about this technology. This paper examines the revolutionary potential of CRISPR therapy in medicine, alongside the ethical and moral implications that arise from its application. The potential of the therapy has been placed in a specialised context – how the implementation of CRISPR-Cas9 could impact sportsmen and -women, especially those battling such hard genetic diseases as Paralympians in different disciplines do every day. By analysing the scientific advancements, potential applications, and ethical dilemmas, a comprehensive understanding of CRISPR’s impact on contemporary medicine and contemporary sports is developed.